Social Influence as a Major Factor in Smart Meters’ Acceptance: Findings from Brazil - Gumz, Jonathan; Fettermann, Diego Castro; Sant’Anna, Ângelo Márcio Oliveira; Tortorella, Guilherme Luz (Results in engineering, 2022)
Smart meters are IoT devices that play a central role in smart cities. However, consumers' acceptance of these smart meters is crucial for the smart meter'’s implementation and sustainable use of resources. Despite the need to further understand what influences the acceptance of smart meters, only a few studies tackle this issue, none of them in South America. This article seeks to investigate which factors influence the acceptance of smart meters by consumers in Brazil to provide insights into public policies that help in smart meter implementation projects. This work features a survey (N = 144) in the city of Florianópolis, the capital of Santa Catarina, that comprises items derived from research and technology acceptance models, mainly the UTAUT2 model. PLS-SEM method is used to assess the influence relations on acceptance and the moderation of these relations by gender, age, and years of formal education of respondents. Social Influence is estimated as one of the main factors for the acceptance of smart meters in Florianópolis, something not foreseen in previous research on this topic. Another surprising result is the lack of influence from Performance Expectancy. This study presents a detailed acceptance model based on the survey carried out, and specific strategies for public policies are given based on the constructed acceptance model. •Smart meter's implementations highly depend on consumer acceptance.•First research on consumer's acceptance of smart meters in South America.•Social influence is the main factor to acceptance of smart meters in Brazil.•The article provides important insights on public policies for smart meter implementation.